Implementasi Teori Organisasi dalam Pengelolaan Klinik Utama: Pendekatan Multidimensi - Tyas Utami, Dhian; Feronica Melinda Muskitta; Fanny Fardiyani; Purwadhi; Yani Restiani Widjaja (Universitas Muhammadiyah Surabaya, 2024)
The management of primary clinics, as providers of both primary and secondary healthcare services, faces challenges in achieving operational efficiency, inter-unit coordination, and service quality. This article aims to analyze the implementation of organizational theory in managing primary clinics using a multidimensional approach, encompassing classical, neoclassical, and modern theories. The study examines how classical theory contributes to the establishment of structure and work efficiency, how neoclassical theory enhances interpersonal relationships and employee motivation, and how modern theory, through a systems-based approach, supports the integration of technology and management innovation. This article offers practical recommendations for optimizing primary clinic management through the holistic application of organizational theory.